1991
DOI: 10.1161/01.cir.83.5.1577
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of the epicardium in postinfarction ventricular tachycardia. Observations derived from computerized epicardial activation mapping, entrainment, and epicardial laser photoablation.

Abstract: BACKGROUND Conventionally, monomorphic sustained ventricular tachycardia in patients with remote myocardial infarction is believed to originate from the subendocardium. In a previous study, we demonstrated that electrical activation patterns during ventricular tachycardia occasionally suggest a subepicardial rather than subendocardial reentry. METHODS AND RESULTS This study prospectively evaluated the functional role of the epicardium in postinfarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(50 citation statements)
references
References 56 publications
0
49
0
1
Order By: Relevance
“…Intraoperative mappings and computer simulations of endocardial mappings of patients with ischemic heart disease showed that concealed entrainment could be obtained through stimulation of a region of the reentrant circuit. This results in antidromic blockade of the depolarizing wave by the wave front of the tachycardia, preventing depolarization of adjacent regions and also causes the orthodromic conduction of the depolarizing wave in a similar manner to SVT activation 34,35 . In rare situations, blockade of the stimulation wave may occur orthodromically, allowing antidromic conduction and, consequently, change of the outlet site of the circuit and of SVT morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative mappings and computer simulations of endocardial mappings of patients with ischemic heart disease showed that concealed entrainment could be obtained through stimulation of a region of the reentrant circuit. This results in antidromic blockade of the depolarizing wave by the wave front of the tachycardia, preventing depolarization of adjacent regions and also causes the orthodromic conduction of the depolarizing wave in a similar manner to SVT activation 34,35 . In rare situations, blockade of the stimulation wave may occur orthodromically, allowing antidromic conduction and, consequently, change of the outlet site of the circuit and of SVT morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Celem ablacji przezcewnikowej jest cieśń wolnego przewodzenia (cieśń krytyczna) w obrębie obwodu pobudzeń nawrotnych generującego VT. Ten obwód pobudzeń nawrotnych może mieć wielkość kilku centymetrów i obejmować wsierdzie, śródsierdzie lub nasierdzie w obrębie złożonej trójwymiaro-wej struktury [192,193]. Częstoskurcz komorowy związany z blizną w mięśniu sercowym jest typowo jednokształtny, ale u tego samego pacjenta może występować VT o wielu różnych morfologiach.…”
Section: Pacjenci Z Blizną W Mięśniu Sercowymunclassified
“…However, the main limitation of the study of Di Biase et al was that the ablation technique differed between groups: scar homogenization in the epi-group versus limited substrate ablation in the historical cohort. Our series includes not only electrical storms but all patients with sustained monomorphic VTs, and the same ablation technique was used in both groups.This systematic endo-epicardial approach in IHD patients could be justified by some arguments: (a) different data point to increased electrophysiologists confidence with the technique that probably reflects the improvement in terms of security and the awareness of the extent of epicardial involvement 7 ; (b) epicardial and intramural re-entry circuit locations are well recognized in the literature [12][13][14] and are an important cause of failure of endocardial ablation 6 ; (c) improvements in outcome have been demonstrated when patients undergo an endo-epicardial ablation in a second procedure after a first only endocardial ablation has failed 5 ; (d) clinical and EKG characteristics have failed to reliably identify endocardial or epicardial components of VT circuit in IHD. 15 So we speculated that an appropriate choice of a combined endo-epicardial approach as a first line mapping, and ablation strategy may avoid a substantial number of repeated procedures and improve ablation outcome, as it has been demonstrated.…”
mentioning
confidence: 99%